Eco-Labels and Green Purchasing Behaviors: The Mediating Role of Environmental Knowledge and Trust - Cavusoglu, Sinan (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study examines how eco-labels shape green purchasing behavior by focusing on two key mechanisms: consumers’ general environmental knowledge and their trust in eco-labels. Survey data were collected from 390 volunteer consumers who self-identified as eco-consumers, and the proposed relationships were tested in SmartPLS using a partial least squares structural equation modeling approach. The results indicate that eco-labels are positively related to both general environmental knowledge and trust in eco-labels. Mediation tests further show that these two variables jointly provide a positive partial pathway through which eco-labels translate into stronger green purchasing behavior, rather than operating as simple on-pack cues. Practically, the findings suggest that brands should treat eco-labels as part of their broader branding strategy: labels need to communicate clear, specific, and verifiable sustainability claims, supported by recognizable certification information and consistent messaging across touchpoints. When eco-labels rest on credible, transparent, and easy-to-check standards, government agencies and certification bodies can also strengthen consumer confidence and reduce skepticism, which in turn can improve the effectiveness of policy initiatives aimed at increasing green purchasing. In addition, improving consumers’ baseline environmental knowledge through public information campaigns, retailer education, or brand-led content can amplify the impact of trustworthy labels by helping shoppers interpret certification cues and compare products more confidently. Overall, the study highlights that well-designed eco-label systems can build trust, inform consumers, and encourage meaningful shifts toward greener purchasing decisions.